2012
DOI: 10.1210/jc.2011-1798
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Lipid Accumulation and Reduced Glucose Tolerance in Elderly Adults Are Accompanied by Altered Skeletal Muscle Mitochondrial Activity

Abstract: Elderly adults show evidence of altered mitochondrial activity along with increased adiposity, oxidative stress, and reduced glucose tolerance, independent of obesity. We propose that mild uncoupling may be induced secondary to age-associated oxidative stress as a mechanism to dissipate the proton-motive force and protect against further reactive oxygen species production and damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 34 publications
5
76
2
Order By: Relevance
“…The significance of IMCL is controversial, with some studies suggesting that muscle lipid accumulation is an early and critical event in the development of insulin resistance [28]. In contrast, similar to Thomas et al [29], we found no correlation between IMCL and liver fat and, like Machado and colleagues [9] we found no relationship between IMCL and muscle mitochondrial dysfunction [6,26].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The significance of IMCL is controversial, with some studies suggesting that muscle lipid accumulation is an early and critical event in the development of insulin resistance [28]. In contrast, similar to Thomas et al [29], we found no correlation between IMCL and liver fat and, like Machado and colleagues [9] we found no relationship between IMCL and muscle mitochondrial dysfunction [6,26].…”
Section: Discussionsupporting
confidence: 65%
“…In a related study in a cohort of insulin-resistant offspring, a reduction in muscle mitochondrial density (measured in muscle biopsy specimens) was accompanied by increased IMCL, reduced insulin-stimulated glucose uptake and impairment of insulin signal transduction [24]. In the elderly, the same relationship was observed between claimed measures of mitochondrial dysfunction, ectopic fat accumulation and insulin resistance [6]. However, proposals of a causal relationship between muscle mitochondrial dysfunction, increased muscle cellular triglyceride accumulation and disordered post-receptor insulin signaling have been called into question by animal [25] and human [26] studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A decline in organelle content is supported by many studies that report reduced enzymatic activities [i.e., citrate synthase, cytochrome oxidase (COX) activity] and protein markers (21, 102, 147, 148), mtDNA content (78,166), along with electron micrograph evidence of diminished IMF mitochondrial size and a reduced thickness of the SS mitochondrial layer (FIGURE 1) (68). Furthermore, mitochondrial functions are impaired with aging (54,72), including reduced mitochondrial protein synthesis (138), respiration (11,161), and maximal ATP production rate (MAPR) (89, 147), partly a result of increased uncoupling of oxygen consumption to ATP synthesis (FIGURE 2) (29, 71,107). Importantly, some of these declines have been noted even when physical activity levels between young and old subjects have been carefully matched (45,71,89,138,147), suggesting true age-related deficits in mitochondrial function.…”
Section: Aging and Mitochondriamentioning
confidence: 99%
“…Furthermore, mitochondrial functions are impaired with aging (54,72), including reduced mitochondrial protein synthesis (138), respiration (11,161), and maximal ATP production rate (MAPR) (89, 147), partly a result of increased uncoupling of oxygen consumption to ATP synthesis (FIGURE 2) (29, 71,107). Importantly, some of these declines have been noted even when physical activity levels between young and old subjects have been carefully matched (45,71,89,138,147), suggesting true age-related deficits in mitochondrial function. However, this conclusion remains controversial, since some studies have reported no changes in mitochondrial respiratory function with age or have noted that the changes are muscle type-specific and related to motor unit recruitment patterns and levels of physical activity (72,80,89,127).…”
Section: Aging and Mitochondriamentioning
confidence: 99%